AN ANALYSIS OF FLRA TO EFL LEARNERS AT IKIP SILIWANGI - Sakina Mawardah; Farah Hana Zinan; Iman Santoso (PROJECT (Professional Journal of English Education), 2019)
This study is aimed to know the scale on the level of anxiety on Foreign Language in general and in reading on EFL learners especially to English department learner of 2015 in IKIP Siliwangi Bandung. The method that is used in this research is descriptive qualitative. The data were gathered using an online form by using a Likert scale questions of FLRAS (Foreign Language Reading Anxiety Scale) and FLCAS (Foreign Language Classroom Anxiety Scales). The data that have been collected were then analyzed using IBM SPSS Statistics 22 that consisted of descriptive statistics (e.g. means, standard deviations, percentages, etc.). The data used to measure the level of FL anxiety in general and in reading. From the results, more than 66% of the EFL learners have a medium-level in FLRAS, and 76% of the participant has a level of mildly anxious in FLCAS toward English as a foreign language.